Early identification of crosscutting concerns with the Language Extended Lexicon - Antonelli, Leandro (2015)
Large-scale software applications are complex systems that involve a myriad of different concerns. Ideally, these concerns should be organized into separated and different modules, but often some of these concerns overlap and crosscut each other. Such a situation is problematic, as concerns are tangled and scattered into different modules; thus, design and source code become difficult to produce and maintain. The Modularity community has been addressing crosscutting concerns by developing techniques based on separation of concerns. This separation must be done as early as possible during software construction to obtain a more modular and consequently better maintainable software, where evolution is performed with less effort and the possibility of introducing unforeseen mistakes is minimal. In this paper, we propose a strategy to identify crosscutting concerns at requirements level, i.e., at early stages in the software development process, by using the Language Extended Lexicon.